PEMBAGIAN KERJA BERDASARKAN JENIS KELAMIN DALAM RUMAH TANGGA PETANI PADA PENGELOLAAN KEBUN KARET DI DESA PURWOSARI KECAMATAN SEMBAWA BANYUASIN SUMATERA SELATAN - , UMBAR RIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study was aimed to understand the physiographic, accessibility and social-economic condition of research area. These factors were put as inputs of resemblance and disparity work allocation analysis and time outpouring between household-housewife farmer at rubber plant. Location of the research was in Purwosari village which is located at Sub District Sembawa, Banyuasin Regency, South Sumatra Province. Data were collected using in-depth interviews. The informants included tenant farmers and rubber plantation owners, chairman GAPOKTAN, and Purwosariâsofficials staff. This in-depth interview data was analyzed using descriptive qualitative to show time outpouring representation in rubber plantation management. The result discovered that Purwosari has characteristics relatively flat environment, good accessibility, predominantly dry land/garden, varied economic activities and land use is dominated by things related torubber plantations, so this condition supports the rubber plantations management. The average land holding of rubber farmers are 2 hectares. On the rubber plant management, the husband is being the main actor that dominates the entire workof rubber plantations management since its early planting, harvesting and marketing. Mean whie the wife was outpouring less of time than the husband in the rubber plantations management.